The Effect of Work Discipline, Organizational Culture, and Work Environment on the Performance of State Civil Apparatus at the Tourism and Culture Office in Karawang Regency - Fitri Rasdayanti; Sonny Hersona; Hartelina Hartelina (Dinasti Publisher, 2023)
This study has purpose to explore further and reveals the effect of work discipline, organizational culture and work environment towards the performance of State Civil Apparatus at the Tourism and Culture Office of Karawang Regency. The process of this research is conducted through descriptive and verification methods. Research population were gathered from whole employees at the Tourism and Culture Office of Karawang Regency with totaling of 83 people. Samples were collected by non-probability sampling technique with the same number of samples and population, namely 76. As for analytical techniques used were scale-range analysis and path analysis techniques which earned results that 1) Work discipline brought significant effect on performance 2) Organizational culture has significant influence against the performance 3) Work environment has significant effect on performance 4) So all of variables namely Work discipline, organizational culture and work environment Jointly affect the performance.